Teacher resilience instrument: Development and validation of a four-factor model - Al-Munnir Abubakar; Fauziah Md Jaafar; Tengku Faekah Tengku Ariffin (Institute of Advanced Engineering and Science, 2022)
The study into teacher resilience has been inadequate due to a lack of measures that apply to educational settings. The items measuring teacher resilience were constructed through literature extensive discussion with the experts in the field and further discussion with the practitioners, i.e., secondary school teachers. The Teacher Resilience Instrument was then tested in a field via survey research method. The sample of the current study consists of 380 secondary school teachers in Bauchi State, Nigeria, through cluster sampling and systematic sampling method. The exploratory and confirmatory factor analysis were used to test the hypothesized model with four dimensions of teacher resilience. The study confirmed that the proposed model was fit and data loading were significant, which leads to the construct validity of the research instrument. Finally, the study highlighted the importance of researching more on teacher resilience to seek its relationship with other factors, pertinent especially to address issues regarding teacher wellbeing and retention.